Princezná : Odvaha a dobré srdce : zbierka rozprávok - Davis, Kathy Ellen; Carbone, Courtney; Liu, Cynthia; Rudnick, Elizabeth; Richards, Kitty; Orsi, Tea; Schmidt, Rebecca; Webster, Christy (Egmont, 2021)
Príbehy o odvážnych princeznách s dobrým srdcom.